Assessment of gastric pouch blood supply with indocyanine green fluorescence in conversional and revisional bariatric surgery: a prospective comparative study - Francesco Mongelli; Fabio Garofalo; Pietro Giacopelli; Martino Munini; Francesco Volontè; Michele Marengo (Scientific Reports, 2023)
Abstract Our study aimed to evaluate the usefulness of indocyanine green (ICG) angiography during conversional or revisional bariatric surgery. We prospectively enrolled all patients scheduled for reoperative bariatric surgery with gastric pouch resizing and ICG assessment and we compared them with a retrospective series of similar patients who did not receive ICG. The primary outcome was the rate of intraoperative change in the surgical strategy due to the ICG test. We included 32 prospective patients receiving intraoperatively an ICG perfusion test and 48 propensity score-matched controls. The mean age was 50.7 ± 9.7 years, 67 (83.7%) patients were female, and the mean BMI was 36.8 ± 5.3 kg/m2. The patient characteristics were similar in both groups. The ICG angiography was successfully conducted in all patients, and no change of the surgical strategy was necessary. Postoperative complications were similar in both groups (6.2% vs. 8.3%, p = 0.846), as well as operative time (125 ± 43 vs. 133 ± 47 min, p = 0.454) and length of hospital stay (2.8 ± 1.0 vs. 3.3 ± 2.2 days, p = 0.213). Our study suggested that ICG fluorescence angiography might not have been useful for assessing the blood supply of the gastric pouch in patients who underwent reoperative bariatric surgery. Therefore, it remains uncertain whether the application of this technique is indicated.